Law Enforcement That Ensures The Achievement Sustainable Environment - Rubiyo Rubiyo (Universitas Negeri Semarang, 2024)
Environment life is unity space and all objects , which exist inside it including human beings . Along with increase human , then will need land For settler , place business For fulfil need primary life and secondary . issues damage environment consequence from logging forest . Research objectives This about issue enforcement law environment sustainable living . Research methods with approach legal normative data source from studies literature journals and books as well as document from and damage forest obtained​ from the internet. Conclusion of enforcement the law that guarantees achievement environment sustainable living , to be effective need collaboration from all party between apparatus enforcer law , government center and regions that have them territory forest . Police as mentor PPNS investigators need existence clarity authority in enforcement law damage environment . Awareness public need built to obey to rules and participate as well as guard environment .